Thermal sizing of low voltage aerial bundled conductors feeding stochastic domestic electrical loads - Theron, Rossouw(Daniel Rossouw) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1995.